Revolutionary text social psychology of cellphone texting during people power II. [article]. - Montiel, Cristina Jayme
In January 2001, Filipinos toppled a corrupt president through People Power II, Using one technological tool to maximum advantage-the mobile phone. The short messaging service(SMS) orn text messaging provided opportunities to pass on messages rapidly to large groups of people. A content analysis of the text messages revealed three themes, namely: political information and persuasion, protest humors and political emotions. Political information included rumors and beliefs, persuasive messages to join mass actions, and practical instructions about mobilizing huge protest rallies. Political jokes passed around permitted Filipinos to derogate President Estrada and his allies, and provided opportunities to ventilate pent-up social angers. Texting during People Power II demonstrated the mobile phone's capacity to disseminate political messages in a rapid, multiplicative, yet discreet fashion, resulting in a massive and peaceful social force. -- (from the author)